2020
DOI: 10.1108/ebr-10-2019-0258
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional approach to the outcomes of perceived value in business relationships

Abstract: Purpose This study aims to explore the relationships, direct and indirect, between business customers’ perceived value, satisfaction and loyalty. Design/methodology/approach The study was set in the business banking industry, with data collected from 381 micro-enterprise business customers of a large South African bank by means of a self-administered, internet-based questionnaire. Findings The results reveal that business customers’ perception of value results in both economic and non-economic satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 92 publications
(158 reference statements)
0
10
0
Order By: Relevance
“…Our cross-sectional approach suffers also from its implicit assumption that the underlying constructs are static, which goes counter to some evidence that conceptualizing and measuring customer-perceived value is individually, subjectively and socially constructed and evolves dynamically (Payne and Holt, 2001; Stępień, 2017; Zietsman et al , 2020). Recent works on the service-profit chain building upon longitudinal data point to such interesting potential dynamic relationships, taking into account customer perceptions of service performance (Strydom et al , 2020).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our cross-sectional approach suffers also from its implicit assumption that the underlying constructs are static, which goes counter to some evidence that conceptualizing and measuring customer-perceived value is individually, subjectively and socially constructed and evolves dynamically (Payne and Holt, 2001; Stępień, 2017; Zietsman et al , 2020). Recent works on the service-profit chain building upon longitudinal data point to such interesting potential dynamic relationships, taking into account customer perceptions of service performance (Strydom et al , 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Future work may, therefore, more extensively focus on feedback mechanisms related to customer innovation perceptions, distinguishing specific types of user-producer interaction that have been identified by Nahuis et al (2012), while also taking into account the types of Behavioral outcomes technologies that differ in the degree to which they are customizable to user demands (Nahuis et al, 2012;Wijekoon and Salunke, 2018). Our cross-sectional approach suffers also from its implicit assumption that the underlying constructs are static, which goes counter to some evidence that conceptualizing and measuring customer-perceived value is individually, subjectively and socially constructed and evolves dynamically (Payne and Holt, 2001;Stępie n, 2017;Zietsman et al, 2020). Recent works on the service-profit chain building upon longitudinal data point to such interesting potential dynamic relationships, taking into account customer perceptions of service performance (Strydom et al, 2020).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 90%
“…Customer orientation is linked to the organisation's capacity of involving its customers continuously and actively, moving the focus from the offer to the entire customer experience. The outcome is to create and maximise long-term value (Fader 2012;Ghouri et al 2021b;Kumar and Sharma 2018;Lamberti 2013;Zietsman et al 2020) in profitability and sustainable competitive advantage (Day 2000), as well as to increase business value (Loshin and Reifer 2013). Cultivating long-term dialogue with customers drives decision-making processes (Prahalad and Ramaswamy 2004), build loyalty and customer retention (Bolton 2004) and support growth in revenue (Simon et al 2016).…”
Section: Customer Valuementioning
confidence: 99%
“…It was shown that there was an inverse correlation between environmental concern, perceived value, and desire to return to green resorts when the SET was used as a foundational theory. The SET postulates the willingness to exchange if one receives a reward and when benefits outweigh costs (Zietsman et al, 2020). Essentially, SET considers the exchange as the basis of human behaviour (Nunkoo, 2016).…”
Section: Theoretical Contributionsmentioning
confidence: 99%